2016
DOI: 10.1016/j.ijantimicag.2016.08.018
|View full text |Cite
|
Sign up to set email alerts
|

Resistance profiles to antimicrobial agents in bacteria isolated from acute endodontic infections: systematic review and meta-analysis

Abstract: Infected root canal or acute apical abscess exudates can harbour several species, including Fusobacterium, Porphyromonas, Prevotella, Parvimonas, Streptococcus, Treponema, Olsenella and not-yet cultivable species. A systematic review and meta-analysis was performed to assess resistance rates to antimicrobial agents in clinical studies that isolated bacteria from acute endodontic infections. Electronic databases and the grey literature were searched up to May 2015. Clinical studies in humans evaluating the anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 41 publications
1
22
2
2
Order By: Relevance
“…To inform the current status of antibiotic prescribing behaviors of dentists, including antibiotic types, doses, and durations, we used a 2018 scoping review. 24 We also included input from stakeholders and expert panelists and data on antibiotic sensitivity [54][55][56][57][58] to determine the most appropriate course of action when first-line treatment fails, guidance to avoid recommending antibiotics closely monitor their symptoms and call a dentist or primary care provider if their infection worsens while receiving therapy. Similarly, clindamycin has a US Food and Drug Administration black box warning for Clostridioides difficile infection, which can be fatal.…”
Section: Summary Of the Rationale For The Type Of Antibiotic And Regimenmentioning
confidence: 99%
“…To inform the current status of antibiotic prescribing behaviors of dentists, including antibiotic types, doses, and durations, we used a 2018 scoping review. 24 We also included input from stakeholders and expert panelists and data on antibiotic sensitivity [54][55][56][57][58] to determine the most appropriate course of action when first-line treatment fails, guidance to avoid recommending antibiotics closely monitor their symptoms and call a dentist or primary care provider if their infection worsens while receiving therapy. Similarly, clindamycin has a US Food and Drug Administration black box warning for Clostridioides difficile infection, which can be fatal.…”
Section: Summary Of the Rationale For The Type Of Antibiotic And Regimenmentioning
confidence: 99%
“…The reasons for their existence inside the root canal would be the presence of sufficient moisture or a water-saturated medium through which they can propel themselves to such distances into the canal, and presence of nutrients to allow them to migrate and survive 'technically' beyond the viable part of the body. Moreover, data from a meta-analysis conducted by Lang et al (2016) suggested a change in resistance patterns of strains isolated from acute endodontic infections in samples of patients who had taken antimicrobial agents before collection. Therefore, the dynamic nature of host/microbial interaction at the apical region and the ecology of the infected pulp cavity should be revisited.…”
Section: Discussionmentioning
confidence: 99%
“…After a review of the literature, as far as we know, there are no studies in the endodontic literature in which the presence of resistance genes is correlated with the different clinical symptoms of resistant infections (secondary endodontic infection). Many studies have only focused on detecting the presence of resistance genes in different oral environments, including bacteria isolated from different types of endodontic infections [35,36]. Other studies have only been dedicated to associate the presence of certain bacterial species with the presence of clinical symptoms [37].…”
Section: Discussionmentioning
confidence: 99%